2016
DOI: 10.1111/jam.13007
|View full text |Cite
|
Sign up to set email alerts
|

Low light intensity and nitrogen starvation modulate the chlorophyll content of Scenedesmus dimorphus

Abstract: The findings acquired in this work are of great biotechnological importance to extend knowledge of choosing the right culture condition to stimulate the effectiveness of microalgae strains for chlorophyll production purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 40 publications
6
35
0
Order By: Relevance
“…It has been shown that high intensity of light exhibits inhibition of pigment content while growing algal cells . It is also reported that low light availability enhanced the chlorophyll content and vice versa . Therefore, it may be stated that these two strains are adopted under low light intensity and accordingly adopted their metabolic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that high intensity of light exhibits inhibition of pigment content while growing algal cells . It is also reported that low light availability enhanced the chlorophyll content and vice versa . Therefore, it may be stated that these two strains are adopted under low light intensity and accordingly adopted their metabolic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, Ferreira et al . () demonstrated an increase in chlorophyll content at 16.91 ± 0.45 μmol photons m −2 s −1 to capture light in a more efficient manner in Scenedesmus dimorphus (UTEX 1237); and Pal et al . () indicated that 1000–1500 lux (6–9 μE m −2 s −1 ) were the best light intensities in order to produce maximum yield in Chaetoceros muelleri (CS‐178).…”
Section: Resultsmentioning
confidence: 99%
“…The elevated chlorophyll content in NSAID treated cultures at the end of the extended exposure (at the 28 th day) was an unexpected phenomenon. Chlorophyll content of microalgal cells could be increased mainly by low light intensity [76][77][78][79], and can be interpreted as shade-adaptation [80]. Although cysts tend to sink to the bottom, which could lead to reduced light availability, the lack of increase in chlorophyll content of all other cultures than NSAID treated ones excludes likely this explanation.…”
Section: Analysis Of Pigment Contentmentioning
confidence: 99%